Transforming Our World--Aiming for Sustainable Development : Using Independent Evaluation to Transform Aspirations to Achievements - Independent Evaluation Group (World Bank, Washington, DC, 2015)
The year 2015 is pivotal in international development. In the lead-up to 2000, the global community came together at various conferences to agree on, for the first time in known history, shared development goals. The eight Millennium Development Goals (MDGs) set 18 targets that were aimed at significantly reducing disease, illiteracy, gender inequality, hunger, and poverty, and improving access to water and sanitation by 2015. Leading up to this point where the era of the MDGs concludes, progress has been monitored and discussions started well ahead of this momentous year to define and meet the more ambitious Sustainable Development Goals (SDGs), building on and bringing to fruition what has been started under the MDG agenda. Much progress has been made toward achieving the MDGs. The world reached the poverty reduction target five years ahead of schedule, and progress has been reported in a number of other areas. However, considerable challenges remain: even while declaring success on MDG1, roughly a billion people remained in poverty. A large number of MDG targets will not be met by the end of 2015, and progress remains uneven among the different countries. Moreover, new challenges to progress are emerging deriving from natural and manmade calamities. To deliver on the twin goals and the post-2015 agenda, the Bank Group would benefit from a clearly articulated role, approach, and expected contribution to the SDGs, both externally for enhancing partnerships and internally to facilitate prioritization and synergies. As this paper has shown, the World Bank Group works actively in many areas relevant to the SDGs, actually many more than covered here, but various evaluations have pointed to the importance of multi-sector integrated approaches that challenge countries and their partners to find new ways of working. The challenges that the SDGs aim to address, and the SDGs themselves, are complex, and solutions will have to be tailored to context, bring together multiple actors, and benefit from dynamic, constantly adjusted planning and execution that is informed by ongoing monitoring and evaluation.